Different response to vitamin D supplementation of PVCs from RVOT and non-outflow tract RV regions. (14th October 2021) - Cismaru, G; Tomoaia, R; Minciuna, I; Lazea, C; Cainap, S.S; Fringu, F; Gurzau, D; Rosu, R; Gusetu, G; Puiu, M; Caloian, B; Comsa, D.H; et al.
Abstract: Background: Recent publications have shown that premature ventricular contractions (PVCs)_ from the right ventricular outflow tract (RVOT) have a good response to vitamin D supplementation in patients that have a vitamin D deficiency. Purpose: The present study aimed to compare the response to vitamin D supplementation of of 2 types of PVCs: from RVOT and from other RV areas outside RVOT Methods: Our study included 16 patients from the Outpatient Clinic of the Rehabilitation Hospital, of whom all had vitamin D deficiency. Four patients had high PVC burden with an RV morphology other than RVOT and were matched 1:3 for age and sex with 12 patients with high PVC burden and RVOT morphology. Results: Mean age was 26 years in both group and 33% were females. The mean 25-OH vitamin D value was 17.7±2.9 ng/ml in the non RVOT group and 21.6±5.3 ng/ml in the RVOT group. After 3±1.7 month of treatment with 2000–5000 U/day, 25 OH vitamin D increased to. 31.1±3.2. in the non-RVOT group and to 35.9±5.1 in the RVOT group. After treatment PVC burden decreased from 19956±2618 to 19399±3015 (NS) in the non-RVOT group and from 21057±9594 to 4249±2835 (p=0.0001) in the RVOT group. Conclusions: After 3 months of vitamin D supplementation in patients with high burden PVC and vitamin D deficiency, the burden decreased significantly by more than 75% in the RVOT morphology group but not in the non- RVOT morphology group. Funding Acknowledgement: Type of funding sources: None.